Differences in the Accuracy of the Inside of the Feet and the Outer Feet in Junior Football Players - Awie Awie; Yohanes Touvan Juni Samodra; Rahmat Putra Perdana; Rubiyatno Rubiyatno; Maharani Fatima Gandasari (Universitas Majalengka, 2023)
The purpose of this study was to determine the calming ability of different parts of the foot in soccer. The research method is a survey of 15 soccer players. The test is to do a precision kick with different sides of the foot: the inside of the foot, the instep, and the outside of the leg. A statistical descriptive analysis was carried out. Based on the results of the research that was carried out with tests of deep leg, instep, and outer leg kicks showing the skill level of Samustida FC players, in doing deep leg kicks, there were 4 players in the very good category and the rest were in that category. The skill level of the instep kick is 4 players in the medium category, and the rest are under that category. Based on the data that has been obtained, it can be concluded that the level of instep kick ability in the very low category is 7%. In the outer leg kick ability category, there are 3 players in the very good category. Based on the data that has been obtained, it can be concluded that the level of leg kick ability is in the less than 20% category.